Borrelia maritima sp. nov., a novel species of the Borrelia burgdorferi sensu lato complex, occupying a basal position to North American species. Issue 2 (3rd December 2019) - Margos, Gabriele; Fedorova, Natalia; Becker, Noémie S.; Kleinjan, Joyce E.; Marosevic, Durdica; Krebs, Stefan; Hui, Lucia; Fingerle, Volker; Lane, Robert S.
Abstract : Borrelia species are vector-borne parasitic bacteria with unusual, highly fragmented genomes that include a linear chromosome and linear as well as circular plasmids that differ numerically between and within various species. Strain CA690 T, which was cultivated from a questing Ixodes spinipalpis nymph in the San Francisco Bay area, CA, was determined to be genetically distinct from all other described species belonging to the Borrelia burgdorferi sensu lato complex. The genome, including plasmids, was assembled using a hybrid assembly of short Illumina reads and long reads obtained via Oxford Nanopore Technology. We found that strain CA690 T has a main linear chromosome containing 902176 bp with a blast identity ≤91 % compared with other Borrelia species chromosomes and five linear and two circular plasmids. A phylogeny based on 37 single-copy genes of the main linear chromosome and rooted with the relapsing fever species Borrelia duttonii strain Ly revealed that strain CA690 T had a sister-group relationship with, and occupied a basal position to, species occurring in North America. We propose to name this species Borrelia maritima sp. nov. The type strain, CA690 T, has been deposited in two national culture collections, DSMZ (=107169) and ATCC (=TSD-160)